Decreased level of antibodies and cardiac involvement in patients with chronic Chagas heart disease vaccinated with BCG - Vicco, Miguel Hernán (2014)
Studies indicate that Trypanosoma cruzi is capable of inducing immunological disturbances such as decreased expression of molecules involved in T-cell survival and costimulation for antigen-driven T-cell responses. On the other hand, several reports have described that BCG vaccination induces a T-helper 1-type immune response with protective effects in different pathologies. In this regard, we evaluated whether BCG vaccination coexists with a better clinical and immunological profile of chronic Chagas heart disease (CCHD). We performed a cross-sectional study in T. cruzi seropositive patients categorized according the BCG vaccine background and to the well-established CCHD classification provided by Storino et al. All individuals were subjected to a complete clinical examination. All patients presented detectable levels of autoantibodies anti-p2β, anti-B13, anti-FRA and antiparasite homogenate immunoglobulins, which were unrelated to age and sex distribution or blood pressure values. Comparisons according to BCG vaccination revealed that individuals who had not been vaccinated presented higher values of antibodies, and patients without BCG vaccine had an OR of 6.1 (95 % CI 1.23?29.25, p = 0.02) for globally dilated cardiomyopathy with reduced ejection fraction (Hosmer and Lemeshow test of 5.2 p = 0.73). Our results suggest that BCG vaccination coexists with a better clinical and immunological profile of CCHD, associated with lower cardiac involvement.